Peculiarities of „social pedagogy” teaching methodics in pedagogic higher educational institutions with using interactive teaching methods - YAKOVLEVA, Valentyna; SAMARIN, Iliia (Journal of Education, Technology and Computer Science, 2013)
In this research paper it is exploring the need of providing interactive teachingmethods into methodological complex of teaching activities of „Social pedagogy”subject for students getting „master” degree in specialty „Pedagogy ofhigher education” on the pedagogic faculty of National University of Life andEnvironmental Sciences. The problem of high dynamics of professional scientificknowledge amount growing is mentioned. Also there is an attempt to findthe way of the problem solving by encouraging the using of modern, interactiveteaching methods